2017
DOI: 10.1021/acs.langmuir.6b04104
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Molecularly Imprinted Reaction Field for [4 + 4] Photocyclodimerization of 2-Anthracenecarboxylic Acid

Abstract: Molecularly imprinted cavities have functioned as a regioselective reaction field for the [4 + 4] photocyclodimerization of 2-anthracenecarboxylic acid (2-AC). Molecularly imprinted polymers were prepared by precipitation polymerization of N-methacryloyl-4-aminobenzamidine as a functional monomer to form a complex with template 2-AC and ethylene glycol dimethacrylate as a crosslinking monomer. The 2-AC-imprinted cavities thus constructed preferentially bound 2-AC with an affinity greater than that toward struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Materials generated by this technique present high chemical resistance, thermal stability, good mechanical properties and reusability [23]. Hence, considering the advantages of MI, many scientists have been using this technique to develop various advanced materials [24][25][26], such as membranes [27,28], beads [29], particles [30,31], micro-and nano-gels [32,33] or thin films [34,35], to be utilized as separation tools [36], catalysts [37] or sensors and biosensors [38] for metal recovery [39,40], drug delivery [41] and ternary mixture separation [42]. In this context, some authors have already reported the use of MI for developing TNT-MIPs using surface imprinting of silica nanoparticles [43] and nanotubes [44] or bulk imprinting of films [16,27].…”
Section: Introductionmentioning
confidence: 99%
“…Materials generated by this technique present high chemical resistance, thermal stability, good mechanical properties and reusability [23]. Hence, considering the advantages of MI, many scientists have been using this technique to develop various advanced materials [24][25][26], such as membranes [27,28], beads [29], particles [30,31], micro-and nano-gels [32,33] or thin films [34,35], to be utilized as separation tools [36], catalysts [37] or sensors and biosensors [38] for metal recovery [39,40], drug delivery [41] and ternary mixture separation [42]. In this context, some authors have already reported the use of MI for developing TNT-MIPs using surface imprinting of silica nanoparticles [43] and nanotubes [44] or bulk imprinting of films [16,27].…”
Section: Introductionmentioning
confidence: 99%
“…Organic templates can also be used to imprint catalytic cavities with specific shapes to increase selectivity in catalysis. Most experiments in this category have focused on using the sacrificial templating agent during the synthesis of the catalyst. , but there are some examples of imprinting performed via the addition of polymer or sol-gel silica layers to existing catalysts. In one example, an imprinted mesoporous La-doped titania film was prepared to selectively promote the hydrolysis of the pesticide paraoxon: mesoporosity was achieved by using a tri-block copolymer (Pluronic F127) as a micellar template, and molecular imprinting of catalytic cavities by adding a La­(III)-(bis-4-nitro-phenyl-phosphate) complex .…”
Section: Surface Modificationmentioning
confidence: 99%
“…Recently, metal‐free GMICs have been also developed, and they have been shown to exhibit great potential for growing economic profits, protecting the environment, reducing health risks, and increasing sustainability. [ 98 ] In addition, metal‐free and eco‐compatible greenificated molecularly imprinted nanoreactors (GMINs) have been synthesized via miniemulsion polymerization prior to their direct application in multicomponent reactions. [ 99 ] Under solvent‐free conditions, these GMINs produced excellent product yields, and multisubstituted imidazole derivatives were achieved in good purities.…”
Section: Catalysismentioning
confidence: 99%